IMPLEMENTASI KEWENANGAN PEMERINTAH DAERAH BERDASAR UNDANG-UNDANG NOMOR 22 TAHUN 1999 - W.M. Herry Susilowati (Perspektif, 2004)
acquired by means of attribution, delegation and mandate, emphasized on accomplishment of decentralization principles by means of domestic arrangement system that is materially, formally and tangibly implemented. Practically the authority rest on factor of human resources supported by natural resources and availability of sufficient equipment as well as organizations and management that have a satisfactory quality.